Urinary excretion of type IV collagen as an early marker of renal fibrosis in patients with diabetes mellitus - Irina Arkad'evna Bondar' (Endocrinology Research Centre, 2011)
Aim. To determine the diagnostic value of urinary excretion of type IV collagen in patients with type 1 diabetes with different stages of nephropathy.Methods. Urinary type IV collagen was determined in 60 patients with type 1 diabetes (23 with normal albuminuria, 28 with microalbuminuriaand 9 with macroalbuminuria) by an enzyme immunoassay. 10 healthy individuals were acted as the control group. Renal biopsy was performedin 22 patients. Deposits of type IV collagen were revealed by 11 individuals by immunohistochemistry. Results. The urinary excretion of type IV collagen increased with severety of diabetic nephropathy, correlating with the urinary albumin/creatinineratio, serum creatinine and parameters of daytime and nighttime systolic and diastolic blood pressure. Patients with excessive accumulation of typeIV collagen in the glomeruli had significantly higher level of type IV collagen in the urine. Conclusion. The determination of urinary type IV collagen can be used for early detection of renal fibrosis in patients with type 1 diabetes.